THE IMPORTANCE OF EDUCATIONAL GAMES IN TEACHING FOREIGN LANGUAGES TO CHILDREN IN PRESCHOOL EARLY: PROBLEMS AND SOLUTIONS - Karimov, Davron (Maktabgacha taʼlim jurnali, 2021)
The process of globalization requires people to learn several foreign languages ​​in addition to their mother tongue. Current research shows that it is more effective to start this process at an early age. In our country, too, special attention is paid to this issue, programs are being developed on the basis of a new approach to teaching foreign languages, especially English, in cooperation with the world’s leading organizations and universities. In the last 3 years, this process has been particularly evolving in preschool education. Large-scale projects on teaching English in public and private preschools are being implemented. This article discusses the importance of using educational games in the teaching of foreign languages, especially English, in early childhood, and the ease with which language skills can be easily acquired through a variety of games. Keywords: foreign language, language learning at an early age, educational play, activity, fine motor skills, eye-hand coordination, active learning types, block play in English, role-playing games, manual labor.